Optimization of the temperature of coagulation water bath on processing of the polysulfone membranes for the wastewater treatment of palm oil mill effluent with ultrafiltration process - Said, Aja Avriana Said (Program Studi Teknik mesin, Fakultas Teknik, Universitas Al Azhar Medan, 2024)
Ultrafiltration membranes include a type of porous membrane with a porous size order between 0.01 – 0.1 ?m. The size of the small pores can be made phase inverse. Ultrafiltration is used to separate macromolecules and colloids from their solutions. The ultrafiltrated membrane has an asymmetrical structure with a denser upper layer (the porous size is smaller than the lower surface porosity), so the hydrodynamic retention will be larger. The objective of this study is to optimize the regular coagulation tub on the 19% PSf membrane manufacturing process with DMF solvent and to optimise the performance of the optimum PSF membrane in the processing of liquid waste of the PKS (palm coconut plant) with the ultrafiltration process. In the membrane performance testing process, the materials and tools used are polysulfonic polymers with dimethylformamide (DMF) solvents, whereas the instruments used are a set of ultrafiltration modules consisting of a centrifugal pump, ultra-filtration cell, pressure gauge, barrel, permeation tank, feed tank, and hose. This phase of the study starts with membrane preparation, SEM analysis, initial analysis of PCS liquid waste sample, 19% membrane operation performance test with coagulation bath temperature variable 40; 50; 60 C and adjusting pressure with variation 5; 10; 15; 20; 25 Psi, then determining membrane performance test which is permeability, flow, and rejection coefficients. The results obtained from this study show that a 19% PsfDMF membrane with a coagulation bath temperature of 50 C is the membrane that has the most optimum performance used for the POME wastewater treatment